Management of immune thrombocytopenia during pregnancy - Kaveri; Nahid, Mohammadi; Shali, Sohail (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Immune thrombocytopenia or Idiopathic thrombocytopenic purpura (ITP) is the most common cause of thrombocytopenia in the first and second trimesters of pregnancy. The diagnosis and subsequent management of ITP in pregnancy requires a multidisciplinary approach. The proper evaluation of ITP in pregnancy is essential to anticipate and manage complications. Hence, the management of pregnant women with ITP is usually difficult and complicated. Methods: All patients diagnosed with Immune Thrombocytopenia admitted in the Department of Obstetrics and Gynaecology, Gulbarga Institute of Medical Sciences, Kalaburgi from 01 January 2022 to 31 December 2023 were included in study. Data was gathered through a retrospective chart review of all patients admitted with diagnosis of ITP during this period. Results: 529 women between 18 and 40 years of age with thrombocytopenia were attended. Out of these 14 pregnancies with ITP were managed at our institute. Majority were primigravida with term gestation. Out of 14 cases 9 cases had to receive corticosteroid and 5 cases did not require any treatment. Maternal complications were in form of pre term labour, abruptio placenta and postpartum hemorrhage. Neonatal outcomes were analyzed in terms of pre maturity, low birth weight (LBW), neonatal intensive care unit (NICU) admission and neonatal deaths. Conclusions: ITP is a complex and heterogeneous disorder with an uncertain etiology and pathophysiology. Due to the lack of a gold standard diagnostic test, diagnosis relies on the exclusion of other causes of thrombocytopenia. Standard treatments include corticosteroids and intravenous immunoglobulin (IVIG). However, there are still unmet needs in the management of ITP. Our study suggests that a single course of low-dose dexamethasone is more effective in managing ITP during pregnancy compared to conventional treatments.